Pemanfaatan Singkong (Manihot Esculenta) Sebagai Bahan Utama Dalam Pembuatan Nasi Tiwul Di Desa Sukoharjo - Farizal Imansyah; Puji Syalsyabilah; Wenni Hasrolita; Ilham Kurniawan; Muhrom Adhytia (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
Community service activities carried out by PGRI University Palembang students aim to preserve the traditional food typical of Sukoharjo village, namely tiwul rice and it is hoped that this food can become a business for economic development. This activity was carried out in Sukoharjo Village which is located in Buay Madang Timur District, East Ogan Komering Ulu Regency, South Sumatra Province. In its implementation, namely utilizing cassava plants into pure tiwul rice with traditional tools and methods, tiwul rice generally has 2 types, namely mixed tiwul rice and pure tiwul rice, the Sukoharjo village community prefers pure tiwul rice because this type has become the traditional food of Sukoharjo village. The skills of the Sukoharjo Village Community in processing cassava into processed ingredients, especially tiwul rice, have increased because this food is an annual tradition of Sukoharjo village, therefore almost all people can make tiwul rice.